Galectin-3 interacts with components of the nuclear ribonucleoprotein complex. Issue 1 (December 2016) - Fritsch, Katharina; Mernberger, Marco; Nist, Andrea; Stiewe, Thorsten; Brehm, Alexander; Jacob, Ralf
Abstract Background The multifunctional β-galactoside-binding protein galectin-3 is found in many distinct subcellular compartments including the cell nucleus. Expression and distribution of galectin-3 between the cell nucleus and the cytosol changes during cell differentiation and cancer development. Nuclear functions of galectin-3 and how they contribute to tumorigenesis are not understood. Methods In order to identify nuclear galectin-3 interaction partners, we used affinity chromatography and co-immunoprecipitation. Spatial proximity in the nucleus was assessed by immunofluorescence and proximity ligation assay. We also investigated the function of galectin-3 on mRNA-export by fluorescencein situ hybridization and on mRNA-processing by RNA-sequencing. Results The heterogeneous ribonucleoprotein particle component hnRNPA2B1 was identified as a novel galectin-3 binding protein that associates with the lectin in a lactose-dependent manner in the cell nucleus. Specific individual depletion of galectin-3 does not affect the mRNA distribution between cytoplasm and nucleus. A significant alteration of this distribution was observed after combined depletion of galectin-1 and −3. However, silencing of galectin-3 was sufficient to alter the splicing patterns of several genes. Conclusions Galectin-3 and hnRNPA2B1 interact as members of the early splicing machinery. Galectin-3 and −1 have redundant functions in mRNA transport and at least in part in mRNA splicing. RNA-sequencing data points to a specific function of the hnRNPA2B1/galectin-3 interaction in the processing of transcripts coding for the nuclear oncoprotein SET.